International business - Shenkar, Oded; Luo, Yadong; Shenkar, Oded; Chi, Tailan (New York, 2008)
The third edition of International Business offers an action-focused, practical approach to the topic, helping students understand the global business environment and its repercussions for executives. The book provides thorough coverage of the field, delving into fundamental concepts and theory; the cultural, political, and economic environment; international business strategies; and even functional management areas. More comprehensive than competing books, International Business includes:Strengthened, expanded global cases, examples, and 'industry' and 'co